AI-powered IoT for COVID-19 - Al-Turjman, Fadi. (Boca Raton, FL : CRC Press, 2021)
The Internet of Things (IoT) has made revolutionary advances in the utility grid as we know it. Among these advances, intelligent medical services are gaining much interest. The use of Artificial Intelligence (AI) is increasing day after day in fighting one of the most significant viruses, COVID-19. The purpose of this book is to present the detailed recent exploration of AI and IoT in the COVID-19 pandemic and similar applications. The integrated AI and IoT paradigm is widely used in most medical applications, as well as in sectors that deal with transacting data every day. This book can be used by computer science undergraduate and postgraduate students; researchers and practitioners; and city administrators, policy makers, and government regulators. It presentsa smart and up-to-date model for COVID-19 and similar applications. Novel architectural and medical use cases in the smart city project are the core aspects of this book. The wide varietyof topics it presents offers readers multiple perspectives on a variety of disciplines. Prof. Dr. Fadi Al-Turjman received his PhD in computer science from Queen's University, Kingston, Ontario, Canada, in 2011. He is a full professor and research center director at Near East University, Nicosia, Cyprus.
OCLC-licensed vendor bibliographic record.
Keywords: COVID-19 (Disease); Artificial intelligence -- Medical applications; Internet of things -- Health aspects; COMPUTERS / Data Processing / Parallel Processing; COMPUTERS / General; MEDICAL / Infectious Diseases